Damages under the CISG - selected problems - Buschtoens, Corinna (Department of Commercial Law, 2014)
This paper addresses different contentious issues arising in the context of the right to damages under the CISG. The paper will therefore start with a brief description of the CISG, Art. 74 CISG et seq. as the basic provision on damages in the Convention and Art. 7 CISG as the provision regulating the interpretation and gap-filling of the Convention. Subsequently, selected specific problems of damages will be examined in Chapter III. Where thought appropriate, the paper will give a brief outline of how the specific question is regulated in domestic laws, followed by an overview of the debate on the issue under the CISG among courts and scholars, ending with the author's own position.